Proposed Performance Management System (PMS) using performance prism indicators case study at NGO XYZ - Nabilla, Faradhina Astri; Wibisono, Dermawan (Jurnal Bisnis dan Pemasaran Digital, 2025)
Purpose: The NGO XYZ, a prominent Indonesian NGO, faces the dual challenge of demonstrating accountability and sustaining growth in the competitive philanthropic sector. This study proposes a Performance Management System (PMS) tailored to NGO XYZ using the Performance Prism framework, which emphasizes stakeholder satisfaction, contributions, strategies, processes, and capabilities. Method: This research utilizes qualitative and quantitative methods, including organizational analysis, stakeholder interviews, and the Analytic Hierarchy Process (AHP), to identify and prioritize key performance indicators (KPIs). Results: These indicators span multiple stakeholder groups including donors, beneficiaries, employees, regulators, and suppliers. This study highlights the importance of metrics such as donor growth, program impact, and regulatory compliance in aligning NGO XYZ’s strategic objectives with its operational practices. The key findings reveal that donor satisfaction and retention, beneficiary empowerment, and employee productivity are critical for enhancing the performance of NGO XYZ. The research identifies gaps in innovation, donor engagement, and program sustainability and recommends strategic interventions to address these challenges. Conclusions: Enhancing NGO XYZ’s performance requires a multifaceted approach that prioritizes donor engagement, employee development, and technological innovation. Strategic alignment with community needs and stakeholders further ensures long-term program sustainability and impact. By integrating personalized services, digital tools, and continuous capacity building, XYZ can improve operational efficiency and maintain a competitive edge in the nonprofit sector. Limitations: This analysis is limited by the absence of longitudinal data and direct stakeholder feedback, which may restrict the depth of insights into long-term effectiveness. Contributions: This conclusion offers a strategic roadmap for nonprofit organizations aiming to improve performance through integrated stakeholder engagement, digital transformation, and capacity development.